Perspectives on the use of Verbenone to protect pine seed production from attack by Conophthorus spp (Coleoptera: Curculionidae, Scolytinae) - Del Rio Mora, Adolfo Arturo (Arthropods, 2015)
In three study sites in the Michoacan State, Mexico, we tested five behavioral chemicals: Pityol, 4 Allylanisole, Verbenone (3M MEC), Conophthorin and Hexenol, in several field trials mixed at six combinations or treatments as posible repelents for females of Conophthorus conicolens W and Conophthorus teocotum W. Beetle-host tree combinations included these two cone bores species on cones of Pinus pseudostrobus (Lidl), the first, and on Pinus teocote (Schl and Cham) the second ones, baited previously with five semiochemicals, including the only case of Verbenone (3 M Mec) which was sprayed alone on healthy green cones of second year growing free from the presence of cone borers and previously to fly period of scolitids as at all other treatments. Cones baited with the combination of semiochemicals P+4AA+V besides these sprayed with Verbenone were less attacked and obviously distinctibily. Moreover, cones baited only with Pityol and adding Verbenone as a spray periodically, the effect of treatment was inefficient to protect them from boring by Conophthorus conicolens W, whereas these baited with P+4AA synergized the presence of cone borer females; The combination of all these semiochemicals and added with Conophthorin (P+4AA+C) and Hexenol (P+4AA+H) had inconsistent results, although for this last case, Hexenol apparently was synergist when is mixed with Pityol and 4AA , to prevent from attack by Conophthorus teocotum W. The best results of study subject were obtained with the combined treatment Pityol +4AA+Verbenone, and significately better spraying as alone as Verbenone and repelling C. conicolens W and C. teocotum W.